O habitante e o habitat : a casa senhorial da Corte, da abertura dos portos ao fim do Império - Bosi, Felipe Azevedo (2015)
Based on a teleology of the Brazilian habitat, this study aims to understand better the formation of our house, starting from the housing of the Joanino period until the end of the empire. The space is studied here by the optic of private life history and